Metamorphoses Resurrection, Body and Transformative Practices in Early Christianity - Seim, Turid Karlsen (Berlin W DE G, 2009)
How were ideas and experiences of transformation expressed in early Christianity and early Judaism? This volume explores the social and philosophical frameworks within which transformative ideas such as resurrection and practices of becoming "a new bein
Keywords: Human body -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600. Change -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600. RELIGION -- Christianity -- General